Home » Aptitude » Algebra » Question
  1. If x + y + z = 6, then the value of (x – 1)3 + (y – 2)3 + (z – 3)3 is
    1. 3 (x – 1) (y + 2) (z – 3)
    2. 3 (x + 1) (y – 2) (z – 3)
    3. 3 (x – 1) (y – 2) (z + 3)
    4. 3 (x – 1) (y – 2) (z – 3)
Correct Option: D

Using Rule 21,
x + y + z = 6
⇒ x + y + z – 6 = 0
⇒ (x – 1) + (y – 2) + (z – 3) = 0
If a + b + c = 0, then a3 + b3 + c3 = 3abc
∴ (x – 1)3 + (y – 2)3 + (z – 3)3 = 3 (x – 1) (y – 2) (z – 3)



Your comments will be displayed only after manual approval.